Peças cerâmicas fabricadas usando pó de granito com adição dos produtos da combustão do carvão mineral: caracterização mecânica - Pinheiro, Halisson de Souza (2019)
The technical feasibility of the use of granite residues as raw material in the manufacture of ceramic test specimens, with additions of the Coal Mineral Combustion (PCC's) products as a reforestation phase, was studied. The materials used were White Wing granite (RGAB) and Coal Combustion Products (PCC), in concentrations of 0% w / w, 5% w / w, 10% w / w, 15% w / P of PCCs. For a characterization of the raw materials and the samples with the techniques of: X-Ray Diffraction, X-Ray Fluorescence, Scanning Electron Microscopy. For a determination of the mechanical properties performed with tests of Vickers Microhardness andDiametral Compression Resistance. Optical microscopy and EDS assays were performed to verify the chemical composition of the surface and the interior of the samples. Statistical analysis of the results (analysis of variance -ANOVA) was analyzed through the Tukey test, which had as objective as sections as arithmetic means obtained in the mechanical testicles were statistically significant. We assigned the number 1, for the pairs in which as means are statistically different, and the number 0, to stop where is not the statistical difference between as means. The results obtained allow to conclude the use of the tailings of the Asa Branca Granite with an addition of PCC to a ceramic coating manufacturing is feasible.